Representatividade das áreas prioritárias e protegidas nas zonas costeira e marinha brasileiras considerando os movimentos das baleias-jubarte, Megaptera novaeangliae (Borowski, 1781) - Castro, Franciele Rezende de (Universidade Federal de Juiz de Fora, 2012)
The establishment of representative systems of Protected Area is part of conservation strategies of humpback whales (Megaptera novaeangliae Borowski, 1781) conservation. This study aimed to evaluate the use of the Priority Areas for Conservation (PACs) and Conservation Units (CUs) by humpback whale along the Brazilian coast. The use was measured by the frequency of positions registered inside the PACs and CUs. Locations data from satellite telemetry were filtered and modeled by State Space Model and overlapped on the PACs and CUs shapes (Ministério do Meio Ambiente - MMA and Instituto Brasileiro do Meio Ambiente e Recursos Renováveis – IBAMA databases). The analyses were performed using the software R 2.11.1 and ArcGIS 9.3. From a total of 131 PACs, recorded in the currently known limit of distribution in the Brazilian coast, 53 Priority Areas for Conservation were used by humpback whales. The frequencies were higher inside the PACs than outside (p<0,001). And from 73 UCs recorded, 13 Conservation Units were used by humpback whales and the frequencies were lower inside the CU’s than outside (p<0,001). We concluded that the PACs identified, areas not yet protected, are representative considering the movement of humpback whales. However, CU’s are still poorly representative for humpback whales conservation considering the low frequency of occurrence of whales in these areas already managed. Satellite telemetry studies are useful to assess the representativeness of Priority and Protected Areas in the conservation of humpback whales indirectly, contributing to strategies for management of the species in Brazilian waters. O estabelecimento de um sistema representativo de Áreas Protegidas é parte das estratégias de conservação das baleias-jubarte (Megaptera novaeangliae Borowski, 1781). Este estudo teve como objetivo avaliar a representatividade das Áreas Prioritárias para a Conservação (APCs) e das Unidades de Conservação (UCs) considerando os movimentos desta espécie na costa brasileira. O uso destas Àreas ...